Automatic sauce dispenser / Mohamad Amin Asyraf Suib & Luqman Hadi Basirun - Suib, Mohamad Amin Asyraf; Basirun, Luqman Hadi (2015)
The Automatic Sauce Dispenser is designed to improvise the ordinary manual sauce dispenser which is commonly used by the fast food restaurant in order to ease their customers. Users always find it hard to push the pump in order to dispense the sauce especially with their hands full of things. This project will at least decrease the burden by only putting the sauce plate in front of the sensor. The circuit design process of this project was done by using Proteus 8 software. It begins with the designing of the circuit until a successful simulation of the circuit was obtained. The circuit was designed by combining three main circuits which is the sensor circuit, the timer circuit and the motor circuit which controlled by three IC for each circuit. Those circuit is then transferred to PCB and the prototype design begins. The design prototype has been fabricated and the output was measured on how much and how long the sauce will dispense. The prototype simulation was ran several times by changing the timer until expected output is obtained. This is to ensure that besides ease the users, this project can also reduce sauce wastage. After completing this project, it is observed that the sauce wastage is reduced and the users was eased after the sensor and timer is added into the sauce dispenser system.